Design and assessment of an efficient and equitable dynamic urban water tariff. Application to the city of Valencia, Spain. (March 2018) - Lopez-Nicolas, A.; Pulido-Velazquez, M.; Rougé, C.; Harou, J.J.; Escriva-Bou, A.
Abstract: Water pricing policies have a large and still relatively untapped potential to foster more efficient management of water resources in scarcity situations. This work contributes a framework for designing equitable, financially stable and economically efficient urban water tariffs. A hydroeconomic simulation model links the marginal value of water, which reflects water scarcity given its competing uses, to water supply reservoir levels. Varying reservoir levels trigger variations in the second block of the proposed two-block increasing-rate tariff; these variations then reflect water's value at that time. The work contrasts the two-block scarcity tariff with a constant volumetric rate for the city of Valencia, Spain, and the drought-prone Jucar basin, where most of 430, 000 households are equipped with smart meters. Results show urban consumption is reduced by 18% in the driest years, lowering basin-wide scarcity costs by 34%. Highlights: Design of equitable, efficient and financially stable dynamic urban water tariffs. Considering the marginal value of water at source for dynamic urban tariffs. Linking the impacts of scarcity-price at river base scale to the user's level.